7+(-1)+12-7=x

Simple and best practice solution for 7+(-1)+12-7=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+(-1)+12-7=x equation:


Simplifying
7 + (-1) + 12 + -7 = x
7 + -1 + 12 + -7 = x

Combine like terms: 7 + -1 = 6
6 + 12 + -7 = x

Combine like terms: 6 + 12 = 18
18 + -7 = x

Combine like terms: 18 + -7 = 11
11 = x

Solving
11 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
11 + -1x = x + -1x

Combine like terms: x + -1x = 0
11 + -1x = 0

Add '-11' to each side of the equation.
11 + -11 + -1x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + -1x = 0 + -11
-1x = 0 + -11

Combine like terms: 0 + -11 = -11
-1x = -11

Divide each side by '-1'.
x = 11

Simplifying
x = 11

See similar equations:

| (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) | | 3(2x-4)=5(x+6) | | 7x-6-4x=4x-3 | | 2.1x+1=7 | | 9x-3x=-26+2 | | 7-7x=29x+21 | | 17X^43=100000 | | 145-13= | | 6x+4-4=20 | | 2(w+6)+4=2w+16 | | 75+13w=335 | | 9m=3(8m+30) | | 10+2x-x^2=0 | | 9x+9=11x-3 |

Equations solver categories